Critical analysis of enablers and barriers in extension of useful life of automotive products through remanufacturing. (1st August 2019) - Chakraborty, Kaustov; Mondal, Sandeep; Mukherjee, Kampan
Abstract: Increasing demand of automotive products and over-consumption of natural resources compel the manufacturers to implement the Extension of Useful Life (EUL) methodology of automotive products through remanufacturing. Remanufacturing is a process in which the original functionality of End-of-Use (EoU) or End-of-Life (EoL) product is restored and the remanufactured product is treated as good as a new product. In spite of these advantages, remanufacturing is still not so popular and organized in developing countries like India. The developing countries encounter several problems in strategic, tactical and operational level of management while implementing the remanufacturing business option. In this paper attempts have been made to identify both the enablers and the barriers in managing business of EUL products through remanufacturing in India. Subsequently the structural relationships among the enablers and barriers have been modelled in this paper. Initially an extensive literature review is carried out to identify the factors depicting the enablers and barriers. Then, Fuzzy Interpretive Structural Modeling (FISM) is applied to develop and evaluate the structural relationships among the identified factors. The application of FISM helps in understanding the effect of major enablers and barriers in extending useful life of automotive products through remanufacturing. The outcome of FISM based analysis shows that low cost, price sensitive market, cheap labour cost, and fast turnaround are the major enablers for OEM in initiating EUL business practice through remanufacturing, whereas the major barriers are lack of proper design of product, stringent foreign trade policy, cannibalization of new product, lack of proper remarketing strategies, lack of reverse network design, lack of proper maintaining the database of the customers, seller reputation and identity. The analysis is further enriched by MICMAC technique, which leads to getting an insight on the significance of the dependence and driving power of both the enablers and barriers.